Cdc42 regulates cell polarization and contractile actomyosin rings during terminal differentiation of human erythroblasts - Ubukawa, Kumi (Sci Rep, 2020)
The molecular mechanisms involved in the terminal differentiation of erythroblasts have been elucidated by comparing enucleation and cell division. Although various similarities and differences between erythroblast enucleation and cytokinesis have been reported, the mechanisms that control enucleation remain unclear. We previously reported that dynein and microtubule-organizing centers mediated the polarization of nuclei in human erythroblasts. Moreover, the accumulation of F-actin was noted during the enucleation of erythroblasts. Therefore, during enucleation, upstream effectors in the signal transduction pathway regulating dynein or actin, such as cell division control protein 42 homolog (Cdc42), may be crucial. We herein investigated the effects of the Cdc42 inhibitor, CASIN, on cytokinesis and enucleation in colony-forming units-erythroid (CFU-Es) and mature erythroblasts (day 10). CASIN blocked the proliferation of CFU-Es and their enucleation in a dose-dependent manner. Dynein adopted an island-like distribution in the cytoplasm of non-treated CFU-Es, but was concentrated near the nucleus as a dot and co-localized with γ-tubulin in CASIN-treated cells. CASIN blocked the accumulation of F-actin in CFU-Es and day 10 cells. These results demonstrated that Cdc42 plays an important role in cytokinesis, nuclear polarization and nuclear extrusion through a relationship with dynein and actin filament organization during the terminal differentiation of erythroblasts.